'Tum Log Yeh Shabd Ke Peechhey Kyon Parh Jaate Ho?': Language, abjection and queer masculinity in Hansal Mehta's Aligarh. (2nd January 2020) - Choudhuri, Sucheta M.
ABSTRACT: This article examines how the representation of abject masculinity resists queer erasure in Hansal Mehta's 2016 film Aligarh . Shortly after the Delhi High Court delegitimized the homophobic Section 377 of the Indian Penal Code, the national media highlighted the assault, suspension and subsequent death of Srinivas Ramachandra Siras, a professor of Marathi literature at Aligarh Muslim University. Aligarh revisits the tragic fate of Siras, whose enforced abjection was catalyzed by not only his sexual orientation, but also the vernacular 'wars' that sanction region-specific forms of masculinity. The film articulates a mistrust of agency implicit in language. The abject male body in Aligarh becomes a source of resistance, rupturing the rigid codification enforced equally by the language of law and by neoliberal discourses of queer activism. Siras's abjection, his insistence on the untranslatability of inchoate feelings and valorization of silences, pauses and emotional excess enacts a subversion of the symbolic order and a return to the pre-linguistic realm. The film posits abject queer masculinity in spectral opposition to postcolonial norms of gender and sexuality.